Các tác giả văn chương Việt Nam - Trần, Mạnh Thường.; Trần, Mạnh Thường. (Hà Nội : Nhà xuất bản Văn hóa thông tin, 2008)
Biographical sketches of Vietnamese authors.
Includes bibliographical references (v. 2, p. 2982-2984)
Text in Vietnamese.
Keywords: Authors, Vietnamese -- Biography; Poets, Vietnamese -- Biography